Optimizing User Experience in Smoothie King’s App: A Capstone Consulting Project - Fernandez Montalvo, Ricardo Steveen (2024)
Smoothie King is enhancing its app to better meet customer needs, focusing on improving payment options by introducing pre-loaded funds. The company is examining customer engagement with the app, including ordering and payment preferences, and gathering feedback for further improvements. Key findings from the research include the need for app updates such as Apple Pay integration, easier navigation, and fixing lagging issues. Customers also expressed a desire for a more robust rewards program. To encourage the use of pre-loaded funds, offering incentives like discounts and free smoothies is recommended. These enhancements aim to boost app usage and customer satisfaction.